2017
DOI: 10.1016/j.adolescence.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Do I fit in? Psychosocial ramifications of low gender typicality in early adolescence

Abstract: The current longitudinal study was designed to examine one of the possible underlying mechanisms that can help account for why low gender typicality (i.e., not feeling like a typical boy or girl) is related to subsequent psychosocial adjustment problems: peer victimization. Relying on a large (N ¼ 5,991, 52% female), ethnically diverse U.S. sample, the results suggested that peer victimization at 7th grade partially accounts for associations between 7th grade gender typicality and 8th grade social anxiety, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Underscoring the effects of school gender climate, these findings extend research demonstrating that individuals’ experiences with lack of peer acceptance (T. E. Smith & Leaper, 2006) gender-based teasing (Jewell & Brown, 2014), and other forms of peer victimization (D. S. Smith & Juvonen, 2017) partly account for associations between gender typicality and socioemotional distress.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Underscoring the effects of school gender climate, these findings extend research demonstrating that individuals’ experiences with lack of peer acceptance (T. E. Smith & Leaper, 2006) gender-based teasing (Jewell & Brown, 2014), and other forms of peer victimization (D. S. Smith & Juvonen, 2017) partly account for associations between gender typicality and socioemotional distress.…”
Section: Discussionsupporting
confidence: 72%
“…Concurrently, both gender-based teasing (Jewell & Brown, 2014) and lack of acceptance (T. E. Smith & Leaper, 2006) have been shown to account for associations between low gender typicality and worse socioemotional outcomes during adolescence, and a similar pattern has been shown over time (D. S. Smith & Juvonen, 2017).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent years, highly-publicized reports of teen suicide (Ducharme, 2018) have drawn attention to bullying and harassment targeting youth because of their sexual orientation, gender identity, or gender expression (SOGIE). Adolescents who are considered, in any way, atypical for their gender often face high rates of peer victimization, and as a result, exhibit poorer mental health, physical health, and academic outcomes relative to their more gender-typical peers (Hill & Kearl, 2011;Jewell & Brown, 2014;Russell, Kosciw, Horn, & Saewyc, 2010;Smith & Juvonen, 2017).…”
Section: Perpetrationmentioning
confidence: 99%
“…Research has also clearly and consistently shown that experiencing GBH is associated with negative outcomes for adolescents. For example, relative to their nonvictimized peers, adolescents who experience GBH on the basis of gender atypicality report lower psychological well-being, such as greater depressive symptoms and more anxiety (e.g., Jewell & Brown, 2014;Mays & Cochran, 2001;Russell et al, 2010;Smith & Juvonen, 2017); more negative academic outcomes, such as lower school satisfaction and lower grades (e.g., Hill & Kearl, 2011;Russell et al, 2010); and more somatic concerns, such as trouble sleeping and loss of appetite (e.g., Espelage, Aragon, Birkett, & Koenig, 2008;Russell et al, 2010;Smith & Juvonen, 2017).…”
Section: Gender and Gender-based Harassmentmentioning
confidence: 99%